Analisis Perbedaan Nilai Konsentrasi Logam Berat Cadmium (CD) pada Rumput Laut (Eucheuma cottonii) di Perairan Pamekasan Dan Sumenep – Madura [Analysis of Heavy Metal Concentration Difference Value on Cadmium (CD) Against Seaweed (Eucheuma cottonii) in Pamekasan and Sumenep Seashore - Madura] - Muhammad Arief; Denny Setiabudi; Boedi Setya Rahardja (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Indonesia is well known as an island nation whose territory is ocean and coastline. One of cultivation are known to have high economic value is seaweed (Eucheuma cottonii). Madura sea is one of the sea that the majority of communities dependent on the seaweed by means of cultivated seaweed in the Madura sea, for the example is E.cottonii seaweed. Seaweed is also useful as a tool to detect the presence of heavy metal cadmium in other organisms, such as scallops, shrimp and fish. The purpose of this research was to determine the difference between the levels of cadmium that accumulates in seaweed E.cottonii on Pamekasan and Sumenep seashore and compared the levels of cadmium in seaweed E.cottonii the provisions of the Indonesian National Standard. Tests performed in the Great Hall of sampling Health Laboratory (BBLK) Surabaya. This research was conducted in Jumiang – Pamekasan seashore, and the Saronggi – Sumenep seashore. The materials used for sampling in this study is E.cottonii wet seaweed with 38 days of age weighing 4.53721 kg at each station in Sumenep and 3.47243 kg at each station in Pamekasan. The main parameters were observed in this research is the sum value of accumulated heavy metal cadmium in seaweed. Auxiliary parameters such as water quality and sediment values in seaweed. On the results of research on the analysis of the difference in value against the concentration of heavy metal cadmium in seaweed E.cottonii on Pamekasan seashore can still be said does not exceed a threshold value that is equal to 0.0182 ppm and 0.0262 ppm. However, The value of the levels of heavy metals in waters declared Sumenep exceeds a threshold value that is equal to 0.1314 and 0.1298.